HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN BEROBAT PENDERITA HIPERTENSI DI PUSKESMAS BALOI PERMAI KOTA BATAM - Dyah Marianingrum; Cevy Amelia (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Hypertension or commonly called high blood pressure is a global health problem, including in Indonesia because of its high prevalence, although it varies in various countries based on data from the Indonesian Ministry of Health shows the prevalence of hypertension in Indonesia reaches 31.7% of the population from the age of 18 years and up. About 60% of people with hypertension end in stroke and this disease affects almost 25% of the adult world population. The purpose of this study is to know the relationship between the level of knowledge and compliance with hypertension treatment at Baloi Permai Public Health Center, Batam City in 2018. research The design of this study was observational analytic with a cross-sectional study approach conducted in this study conducted at the Baloi Permai health center, in Batam City District. The population in this study were all patients with hypertension and samples taken using non-probability sampling techniques with a total of 64 respondents. Data analysis in this study uses chi-square analysis. The results of a study conducted on 64 univariate analysis respondents: there were 38 (59.4%) respondents who lacked knowledge, while those with good knowledge were 26 (40.6%) respondents while Compliance with Medication obtained low compliance results of 43 (67, 2%), moderate as many as 15 (23.4 respondents) and high medication adherence as many as 6 (9.4%) respondents. Bivariate analysis; there is a significant relationship between the level of knowledge and hypertension treatment at Baloi Permai Public Health Center Batam City in 2018 with a value (p-Value = 0.012). There is a significant relationship between the level of knowledge and compliance with hypertension treatment at Baloi Permai Public Health Center, Batam City in 2018. Keywords: Knowledge, Treatment Compliance, Hypertension